173k views
0 votes
Simplify.

5/4+4(3/4−1/2)^2



Enter your answer in the box.

User JGeer
by
5.1k points

1 Answer

1 vote


(5)/(4)+4\left((3)/(4)-(1)/(2)\right)^2=(5)/(4)+4\cdot\left((3)/(4)-(1\cdot2)/(2\cdot2)\right)^2\\\\=(5)/(4)+4\cdot\left((3)/(4)-(2)/(4)\right)^2=(5)/(4)+4\cdot\left((1)/(4)\right)^2\\\\=(5)/(4)+4\cdot(1)/(16)=(5)/(4)+(1)/(4)=(6)/(4)=(3)/(2)=1(1)/(2)

User Jmibanez
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.